The Implementation of Al-Islam and Kemuhammadiyahan Education Curriculum at Muhammadiyah High School in Sorong City - Sijabat, Jenro; Idris, Irfandi; Ekawaty, Rizky (Universitas Pendidikan Indonesia, 2023)
Islamic religious education in Muhammadiyah schools has a distinct characteristic known as Al-Islam Kemuhammadiyahan, which is not present in other public schools. This study aims to describe the implementation of the ISMUBA curriculum, which is a hallmark of Muhammadiyah Al-Amin High School in Sorong City. In this research, a qualitative method was employed, involving the collection of data through document analysis and interviews with ISMUBA teachers, the vice principal in charge of the curriculum, and the school principal. The results of the research conducted at Muhammadiyah Al-Amin High School in Sorong City indicate that the implementation of the ISMUBA curriculum is carried out by integrating the curriculum published by the Ministry of Education and Culture (Kemendikbud) with the central leadership of Muhammadiyah's basic and secondary education council. The subjects covered include Aqidah (Theology) and Morality, Fiqih (Islamic Jurisprudence), Tarikh (Islamic History), Quran and Hadith, Kemuhammadiyahan (Muhammadiyah Studies), and the Arabic language. To support the achievement of the ISMUBA curriculum, integration with school extracurricular activities such as Hizbul Whaton, Tapak Suci (a martial art), Ikatan Pelajar Muhammadiyah (Muhammadiyah Student Association), and Qiroah Al-Quran (Quranic Recitation) is also carried out. These activities are enriched with values and meanings related to Al-Islam Kemuhammadiyahan.